2012
DOI: 10.1080/17518253.2011.585666
|View full text |Cite
|
Sign up to set email alerts
|

Indion 190 resin: efficient, environmentally friendly, and reusable catalyst for synthesis of benzimidazoles, benzoxazoles, and benzothiazoles

Abstract: An efficient and mild protocol has been developed for the preparation of benzimidazoles, benzoxazoles, and benzothiazoles from reactions of aldehydes with o-substituted aminoaromatics in the presence of catalytic amount of Indion 190 resin. Short reaction time, ambient conditions, simple work-up procedure, high yield, easy availability, reusability, and use of an eco-friendly catalyst are some of the striking features of the present protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…For example, in the previously reported work [52], reaction of 2-aminophenol with benzaldehyde or 2-hydroxy benzaldehyde catalyzed by Iodine 190 resin in refluxing ethanol for 4 h afforded 2-phenyl benzoxazole and 2-(2-hydroxyphenyl) benzoxazole in 87% and 83% yields respectively ( This method offered several advantages including excellent yields, high purity, simple reaction conditions, high reaction rates and the easy work up procedures. These results demonstrated that the ultrasound irradiation was an efficient method for the one-pot synthesis of 2-substituted benzoxazoles.…”
Section: Synthesis Of 2-aryl Substituted Benzoxazolesmentioning
confidence: 94%
“…For example, in the previously reported work [52], reaction of 2-aminophenol with benzaldehyde or 2-hydroxy benzaldehyde catalyzed by Iodine 190 resin in refluxing ethanol for 4 h afforded 2-phenyl benzoxazole and 2-(2-hydroxyphenyl) benzoxazole in 87% and 83% yields respectively ( This method offered several advantages including excellent yields, high purity, simple reaction conditions, high reaction rates and the easy work up procedures. These results demonstrated that the ultrasound irradiation was an efficient method for the one-pot synthesis of 2-substituted benzoxazoles.…”
Section: Synthesis Of 2-aryl Substituted Benzoxazolesmentioning
confidence: 94%
“…In continuation of our work in benzimidazole, oxazole and thiazole chemistry [14,19,20] and to understand the effect of ESIPT unit in the photophysical properties of fluorescein moiety, in this paper, we report the synthesis and photophysical properties of novel fluorescein molecules containing thiazole units. The photophysical properties are studied as a function of pH and viscosity.…”
Section: Introductionmentioning
confidence: 98%
“…In this case, the addition of transition metal, namely mercury oxide [9] or lead tetraacetate [16], allows a partial selective synthesis of benzimidazoles. In current years, solvent-free synthesis of benzimidazoles have been reported using Yb (OTf) 3 [18], KSF clay [10], PPA [11], solid-support [13], and iodine mediated in aqueous condition [16], Indion 190 resin [2]. Unfortunately, many of these processes suffer some limitations, such as drastic reaction conditions, low yields, tedious work-up processes and co-occurrence of several side reactions.…”
Section: Introductionmentioning
confidence: 99%